Collision detection based on octree for virtual surgery system. Issue 7 (March 2020) - Hu, Yanrong; Yan, Zhiyuan; Yin, Zhenlun; Du, Zhijiang
Abstract: In the virtual surgery system, the organ is always non-convex and deforms over time which makes the collision detection problem more difficult to handle. In this case, we put forward an innovative collision detection algorithm based on octree. This algorithm can perfectly apply to deal with non-convex organs and organ deformation scenario. In addition, it can achieve high run-time efficiency.